Hak atas Citra Diri dalam Perdagangan Foto Digital: Studi tentang Batas Perlindungan Hukum Perdata - Insani Aulia, Nur; Elmarianti, Elmarianti (Al-Mizan (e-Journal), 2025)
The development of digital technology has introduced a new phenomenon in the form of photo trading on various online platforms such as Fotoyu, Shutterstock, and iStock. Through these systems, photographs featuring human faces can be bought and sold without the knowledge of the individuals depicted. This situation raises legal issues concerning the boundary between a photographer’s copyright and an individual’s personality rights over their own image. This study aims to analyze the Indonesian civil law framework related to the protection of the right to one’s image and to examine the urgency of expanding legal protection for individuals in the digital era. Using a normative legal research method with statutory and conceptual approaches, this study finds that the Indonesian legal system does not explicitly recognize the right to image as a personality right. Existing protections remain scattered across provisions on tort (Article 1365 of the Indonesian Civil Code), the Copyright Law, and the Personal Data Protection Law, all of which are not yet sufficient to address the complexities of digital image trading. Therefore, it is necessary to reform Indonesian civil law to recognize the right to one’s image as part of personality rights, as well as to establish effective oversight mechanisms to ensure the practical implementation of such protections. The results of this study are expected to contribute conceptually to the development of a civil law system that is adaptive to technological advancements and that upholds human dignity in the digital era.